(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The paper puts forward a fundamental question: which rules for ChatGPT? It starts with an examination of the state of the art, which oscillates between the zero rules of the Digital Services Act and the over-regulation of the Proposal for a Regulation on Artificial Intelligence. The Parliament’s amendments to the proposal (May 11th 2023) intervene on some issues: they transform the solitary and quasi-objective accountability of the provider into the chain of accountability between the former and the developer. But grey areas remain in the absence of prior control over the fake information generated by our Chat. The Author concludes by steering the regulatory regime to the goal of combining fundamental freedoms with technical innovation. This work has been developed by Prof. De Minico within the framework of the PNRR MUR Project PE0000013-FAIR.